Pharmacologic Overview of Chlorogenic Acid and its Metabolites in Chronic Pain and Inflammation - Bagdas, Deniz; Gul, Zulfiye; Meade, Julie A.; Cam, Betul; Cinkilic, Nilufer; Gurun, Mine S. (Current Neuropharmacology, 2020)
Background: Natural phenolic compounds in medicinal herbs and dietary plants are antioxidants which play therapeutic or preventive roles in different pathological situations, such as oxidative stress and inflammation. One of the most studied phenolic compounds in the last decade is chlorogenic acid (CGA), which is a potent antioxidant found in certain foods and drinks. Objective: This review focuses on the anti-inflammatory and antinociceptive bioactivities of CGA, and the putative mechanisms of action are described. Ethnopharmacological reports related to these bioactivities are also reviewed. Materials and Methods: An electronic literature search was conducted by authors up to October 2019. Original articles were selected. Results: CGA has been shown to reduce inflammation and modulate inflammatory and neuropathic pain in animal models. Conclusion: The consensus of the literature search was that systemic CGA may facilitate pain management via bolstering antioxidant defenses against inflammatory insults.
Keywords: inflammatory